Review of the Main Parameters for the Development of Antifouling Supports - Jamile de Melo Carvalho; Lilian Lefol Nani Guarieiro (JOURNAL OF BIOENGINEERING, TECHNOLOGIES AND HEALTH, 2026)
Marine biofouling is the process by which organisms such as barnacles, mollusks, algae, and corals attach themselves to submerged surfaces, compromising the performance of structures such as ship hulls, sensors, and pipes. This accumulation increases hydrodynamic resistance, raises fuel consumption, and favors the spread of invasive species. To mitigate these effects, anti-fouling coatings began to be used, initially formulated with highly toxic biocides such as tributyltin (TBT) and triphenyltin (TPT). However, due to the prolonged environmental impacts of these compounds, their use was banned. Given this scenario, alternatives based on natural compounds, polymers, bio-inspired surfaces, and nanoparticles have emerged. This study aimed to conduct a systematic review of the literature to identify the main parameters involved in the development of anti-fouling coatings applied in marine environments. The search was conducted in the ScienceDirect, Scopus, Web of Science, PubMed, and SciELO databases, using the keyword “antifouling,” with no time restriction. Approaches regarding material types, physicochemical properties, evaluation methods, and technical gaps were analyzed. VOSviewer software was used to map trends through keyword analysis. The results indicated a significant growth in publications from 2020 onwards, with contributions from China, the United States, and Brazil standing out. The review identified technological approaches, as well as testing standards that seek to ensure effectiveness, durability, and environmental safety. Despite advances, challenges such as field validation and the long-term durability of coatings remain significant obstacles.